Rekonstruksi Pedagogi Pembelajaran Bilangan Bulat Berbasis Tafsir Al-Qur'an: Integrasi Nilai Ulul Albab, Hisab, dan Mizan dalam Pendidikan Islam - Elis Tuti Winaningsih (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2026)
Mathematics learning at the elementary and secondary education levels remains predominantly procedural, emphasizing mastery of concepts and algorithms rather than fostering reflective thinking and character development. Meanwhile, studies on the integration of Islamic education into mathematics learning have mainly focused on developing instructional materials, whereas the reconstruction of pedagogy grounded in philosophical analysis and Qur’anic exegesis remains limited. This study aims to reconstruct the pedagogy of integer learning from the perspective of Islamic education through philosophical analysis and Qur’anic exegesis. The study employed a qualitative approach using a library research design. Data were collected from the Qur’an, classical and contemporary Qur’anic exegeses, the philosophy of Islamic education literature, and theories of mathematics education. Data were analyzed using the maudhu’i (thematic interpretation) approach, philosophical analysis, and content analysis. The findings indicate that the Qur’anic concepts of ulul albab, hisab, and mizan embody the values of reflective thinking, accuracy, balance, and responsibility, which serve as the foundation for reconstructing mathematics pedagogy. The study proposes a conceptual model consisting of four components: the Qur’anic foundation, pedagogical values, learning strategies, and learning outcomes in the form of mathematical competence integrated with Islamic character. This study contributes to the development of tafsir tarbawi and applied Qur’anic exegesis by demonstrating that the synthesis of Qur’anic exegesis can serve as a philosophical and pedagogical foundation for the development of mathematics learning from the perspective of Islamic education.